New Methodology of Block Cipher Analysis Using Chaos Game - Budi Sulistyo; Budi Rahardjo; Dimitri Mahayana; Carmadi Machbub (Journal of ICT Research and Applications, 2011)
Block cipher analysis  covers randomness analysis and cryptanalysis. This paper proposes a new method potentially used for randomness analysis and cryptanalysis. The method uses true random sequence  concept as a reference for measuring randomness level of a random sequence. By using this concept, this paper  defines  bias  which represents  violation  of  a  random  sequence  from  true random sequence. In this paper, block cipher   is treated as a mapping function of a discrete time dynamical system. The dynamical system framework is used to make  the  application  of  various  analysis  techniques  developed  in  dynamical system  field  becomes  possible.  There  are three  main parts of  the methodology presented  in  this  paper:  the  dynamical  system  framework  for  block  cipher analysis, a  new chaos game  scheme and an extended measure  concept related to chaos game and fractal analysis. This paper also presents the general procedures of the proposed method, which includes: symbolic dynamic analysis of discr ete dynamical system whose block cipher as its mapping function, random sequence construction,  the  random  sequence  usage  as  input  of  a  chaos  game  scheme, output  measurement  of  chaos  game  scheme  using  extended  measure  concept, analysis  the  result  of  the  measurement.  The  analysis  process  and  of  a  specific real or sample block cipher and the analysis result are beyond the scope of this paper.